Deviance: social constructions and blurred boundaries - Anderson, Leon (University of California Press, 2017)
"This sociology of deviance textbook draws on up-to-date scholarship across a spectrum of deviance categories, providing a symbolic interactionist analysis of the deviance process. The book addresses positivistic theories of deviant behavior within a more encompassing description of the deviance process that includes the work of deviance claims-makers, rule-breakers, and social control agents. Cross-cultural and historical treatment of deviance categories provides background for understanding current conceptions of, and responses to, deviance. The book is divided into four parts. Section One introduces students to the sociology of deviance. A sociological approach to deviance is contrasted with popular views of deviants as demonic, mentally ill, and culturally exotic. Sociological methods for studying deviance are described, with particular emphasis on deviance ethnography. Classic positivistic theories of deviant behavior are presented with critique and discussion of revised formulations of the theories. The symbolic interactionist/constructionist approach is presented as a recursive set of processes involving deviance claims-making by moral entrepreneurs, rule-breaking, actions of social control, and stigma management and resistance by those labelled as deviant. Section Two focuses on high consensus criminal deviance, with chapters on murder, rape, street-level property crime, and white collar crime. Chapters in Section Three addresses various forms of lifestyle deviance, including alcohol abuse, drug abuse, and sex work. Section Four examines three categories of status deviance: mental illness, obesity and eating disorders, and LGBTQ identities."--Provided by publisher